Influence of european integration processes on social and economic convergence of regions in Ukraine-Eu cross-border space - Prytula, Khrystyna; Demedyuk, Olha; Kalat, Yaroslava (Współczesne Problemy Zarządzania, 2018)
Having declared the course towards European integration and having signed the EU-Ukraine Association Agreement, Ukraine has made concrete commitments on improving the life of its citizens. It pledges to achieve the level of EU countries’ system of public administration, when the residents’ rights are protected, they have more chances for self-development and are more confident in future. The way to this goal goes through domestic reforms, elimination of corruption, adaptation of European standards, economic integration and political association with the EU. The impact of European integration is already visible in some spheres of country’s activity, mainly in institutional and legislative fields, foreign economic activity of both the country and its border regions and implementation of European instruments in the sphere of cross-border cooperation. However, it is going to take time to observe the influence of European integration on social and economic development of Ukraine and its regions.